Apologies and Compliment Responses: A Case of Pre-service EFL Teachers - Burcu Turhan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
Apology may be defined as “a compensatory action for an offense committed by the speaker which has affected the hearer” (Marquez-Reiter, 2000, p. 44), and a compliment is another speech act "which explicitly or implicitly attributes credit to someone other than the speaker... which is positively valued by the speaker and the hearer" (Holmes, 1986, p. 485). The focus of this paper is to find out which strategies are employed by Turkish pre-service EFL (English as a Foreign Language) teachers while apologizing and responding to compliments especially with equal-status interlocutors, and whether these strategies show differences between females and males. Written Discourse Completion Test (WDCT) was administered to 27 pre-service EFL teachers. The WDCT included six apology and seven compliment response scenarios. The data were analyzed mainly by using the framework of Blum-Kulka and Olshtain (1984) for apologies, and the coding scheme by Ruhi (2006) for compliment responses. Main findings of the study suggest that the participants frequently used the strategy of regret while apologizing, and they preferred to use appreciation strategy while responding to compliments. In addition, chi-square test was applied to see any significant differences between the strategies of females and males in apologizing and responding to compliments. This gender-based comparison resulted in no statistical difference except for only one of the apology scenarios. The overall results imply that investigating pragmatic knowledge of students majoring in ELT through their speech act realizations is vital and may be the first step for organizing appropriate interventions aiming at improving and expanding their pragmatic knowledge.